2016
DOI: 10.1111/jopy.12256
|View full text |Cite
|
Sign up to set email alerts
|

Once a Utilitarian, Consistently a Utilitarian? Examining Principledness in Moral Judgment via the Robustness of Individual Differences

Abstract: Although individual differences in the application of moral principles, such as utilitarianism, have been documented, so too have powerful context effects-effects that raise doubts about the durability of people's moral principles. In this article, we examine the robustness of individual differences in moral judgment by examining them across time and across different decision contexts. In Study 1, consistency in utilitarian judgment of 122 adult participants was examined over two different survey sessions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…18,21,33,34). Importantly, however, even researchers who do not operate within the DPM framework routinely present sacrificial dilemmas research as capturing the core contrast between utilitarian and non-utilitarian ethical approaches, and often make seemingly general claims about the psychological factors and processes that drive 'utilitarian judgment' [30,31], and attribute utilitarian tendencies to individuals [24,32] and specific populations [33,34].…”
Section: Utilitarianism Trolley Dilemmas and Moral Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…18,21,33,34). Importantly, however, even researchers who do not operate within the DPM framework routinely present sacrificial dilemmas research as capturing the core contrast between utilitarian and non-utilitarian ethical approaches, and often make seemingly general claims about the psychological factors and processes that drive 'utilitarian judgment' [30,31], and attribute utilitarian tendencies to individuals [24,32] and specific populations [33,34].…”
Section: Utilitarianism Trolley Dilemmas and Moral Psychologymentioning
confidence: 99%
“…Research employing sacrificial dilemmas regularly report findings about the processes driving or influencing 'utilitarian' judgment [17,20,30,31,61] as well as about the utilitarian tendencies of certain populations [32][33][34]62]. Such claims can suggest a generality and in some cases-as in the initial statements of the DPM-are clearly intended to have such general scope [28,63; though more recent formulations of the DPM are more qualified; see 21].…”
Section: Generality Question: Is There a Meaningful Link Between Pro-mentioning
confidence: 99%
“…Therefore, the dual-process model is better conceptualized as a competition between relatively affect-laden tendencies to reject harm and relatively cognitive tendencies to accept harm to maximize outcomes that require similar processing time. Although experimental manipulations certainly influence responses (e.g., Amit & Greene, 2012), people typically prefer one or the other response by default (Helzer et al, 2016), and stable individual differences reliably predict dilemma judgments (e.g., Bartels, 2008). Thus, not all people may experience strong conflict when encountering dilemmas; many may simply select their default dilemma choice unless they have reason to carefully consider the alternative.…”
Section: Moral Dilemmasmentioning
confidence: 99%
“…Implemental mindsets are typically activated when individuals have already reached a goal decision and start to plan out its implementation. Helzer et al (2017) have shown that individual differences in moral dilemma judgments are relatively stable. Thus, people seem to have a trait-like disposition to favor either utilitarianism or deontology.…”
Section: Discussionmentioning
confidence: 99%